2003
DOI: 10.1097/00005537-200311000-00010
|View full text |Cite
|
Sign up to set email alerts
|

External auditory canal foreign body removal: Management practices and outcomes

Abstract: Emergency room personnel successfully manage the majority of patients with foreign bodies of the external auditory canal. For patients with firm, rounded objects, direct otolaryngology consultation without further manipulation should be strongly considered. Patients who have had previous removal attempts should not undergo further manipulation in the emergency department but rather should be referred directly to an otolaryngologist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
54
1
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 7 publications
(26 reference statements)
5
54
1
8
Order By: Relevance
“…These objects were the most likely to require anesthesia for removal (24%). In the literature the use of anesthetics for removal of ear foreign bodies is also described, especially when unsuccessful attempts had already been made in other departments (6,9,11,14,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…These objects were the most likely to require anesthesia for removal (24%). In the literature the use of anesthetics for removal of ear foreign bodies is also described, especially when unsuccessful attempts had already been made in other departments (6,9,11,14,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…FB in ear can be classified in many ways like organic-inorganic, animate-inanimate, metallic-nonmetallic, hygroscopic-nonhygroscopic, regular or irregular, soft or hard, and so forth, according to their nature [6]. The method of removal usually depends on the type of FB, its position, and cooperation of the patient [7,8]. Based on criteria used by American Family Physician (with Strength of Recommendation Taxonomy (SORT) grade C), all ear FB cases should be referred to ENT specialty for removal except for only those which are directly visible and "graspable" [9].…”
Section: Introductionmentioning
confidence: 99%
“…Many authors found that non-ENT personnel significantly associated with complications and emphasize that difficult or all cases should be managed by an otolaryngologist. [5][6][7] Success depends on the type of foreign bodies, the co-operation of the patient, the type of instrument used and the experience and skills of the ENT surgeon. 7,8 …”
Section: Discussionmentioning
confidence: 99%